Conversação política, incivilidade e intolerância em ambientes digitais - Patrícia Gonçalves da Conceição Rossini (2017)
Everyday political conversation is as a key activity for the proper functioning of democracy and an important precursor to more sophisticated forms of political engagement and participation. It is through political talk that citizens learn about matters of public concern, clarify their own views and access the opinions of others about collective problems. The Internet, as a channel of channels, affords its users with many opportunities to engage in political discussions in various ways. As such, the Internet promotes the extension of the public spheres by fostering the formation of publics that are dynamic, diverse and spread across many platforms. Considering the ever-increasing access to digital news and engagement in on-line political talk, the goal of of this doctoral dissertation is to investigate how people engage in debates triggered by exposure to political news in social networking sites and news sites, with emphasis on how individuals deal with political disagreement and behave in heterogeneous discussion environments. We are specifically concerned with the role of political intolerance in online discussion. By analyzing platforms with different interactive affordances - such as levels of identification, visibility and moderation - we aim at understanding the extent to which digital environments facilitate or constrain certain forms of expression - particularly expressions of incivility and political intolerance. In doing so, we argue that even though uncivil expressions might appear often in on-line political talk, they are not necessarily a threat to democratic values. To sustain this argument, we distinguish uncivil and intolerant behaviors - expressions that deny others of freedom of expression and the right of equal treatment - and analyze the extent to which these behaviors are present in mediated political discussions. We use content analysis to categorize a sample of 12.797 comments from a Facebook page - Portal UOL -, news websites and political blogs. Our results suggest that incivility is widely accepted in different discursive platforms, which in turn reinforces the idea that civility is in the eye of the beholder. Incivility is highly associated with opinion expression and justified opinions, suggesting that uncivil discourse is used as arhetorical asset to express and reinforce - specially in situations of disagreement. Intolerance, however, is seldom observed in all platforms, which in turn demonstrates that even though incivility might be the norm of mediated political discussions, those debates are not characterized by expressions that threaten democratic values and discriminate persons or groups. In this sense, we believe that - albeit uncivil -, mediated political talk should be able to promote the epistemic and social outcomes frequently associated with everyday political talk and should not be dismissed if one aims at understanding the ways technology may impact the political dynamics of democratic societies.